Pembentukan Opini Publik oleh Media: Cable News Network (CNN) Indonesia dalam 2018 North Korea–United States Singapore Summit - Dalila, Alya; Purnama, Chandra (Indonesian Perspective, 2020)
It is undeniable that media is mostly used as a propaganda tool of the political elite to achieve the national interest of its country. This research identifies and explains the establishment of CNN Indonesia in making public opinion as one of the extensions on CNN International regarding the Kim Jong Un and Donald Trump Summit in Singapore in 2018. This research utilized: agenda-setting, priming and framing theory to find out the detail process of forming public opinion by CNN Indonesia. This research also utilizes qualitative research methods based on Robert E. Stake’s explanation. The finding suggests that CNN Indonesia, through its agenda-setting, was able to make the summit has an urgency to be discussed in public. Its priming is able to increasing awareness of the importance of denuclearization and world peace which has been Indonesa’s foreign policy agenda. Through its framing, CNN Indonesia attempted to construct public opinion that the United States able to utilize its super power label in order to perquisite many parties, namely creating the world peace.